PENGARUH KELAS SOSIAL, KEADAAN EKONOMI, DAN KELOMPOK ACUAN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MEREK HONDA BEAT DI KOTA SUNGAI PENUH - Mauledy Ahmad (Al Dzahab: Journal of Economics, Management, Business and Accounting, 2021)
Purpose: This problem is motivated by the widespread problem of people's desire to use motorbikes because motorbikes have become the most practical means of transportation today. People's decisions to make purchases are influenced by various factors such as social class, economic circumstances, and reference groups. Design/Methodology/Approach: Multiple linear regression analysis was chosen as the data analysis tool. The number of samples in this study were 90 respondents. Findings: The results showed that social class and economic conditions had a positive and significant impact on purchasing decisions, while the reference group factors had a negative and significant impact on purchasing decisions. Research implications: Social and economic factors are the determining factors in purchasing decisions, therefore the better the social and economic class of the community, it will affect their decision to purchase a product.